Технология применения системы IDEFO для проектирования системы менеджмента качества - Гуменная, Л. С. (ХНУРЭ, 2009)
There are considered the construction of modeling of a quality management System on the basis of standard IDEFO, the technique and a work order of the description (modeling) of organization’s processes, their definition, classification and identification in the report
Keywords: проектирование системы менеджмента качества; применение системы IDEFO